การเตรียมถ่านกัมมันต์จากไม้ยูคาลิปตัส Eucalyptus camaldulensis Dehnh โดยการกระตุ้นด้วยแก๊สคาร์บอนไดออกไซด์และไอน้ำร้อนยวดยิ่ง - วิจิตร จินดาพันธ์ไพโรจน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
This research was production of activated carbon from Eucalyptus camaldulensis Dehnh. wood by physical activation. The four and five years of wood were used as raw material. The experiment was composed of two steps : the first step was carbonization. The studied variables were temperature and time. The optimum condition was found to be 450 ํC and 45 min. The second step was activation. The investigated variables were effect of temperature, time, particle size and activating agents. The results showed that the optimum condition was 0.3-0.6 mm. of wood at 900 ํC for 150 min. using steam as an activating agent. The characteristics prepared activated carbon was bulk density 0.1809 g/cm3, ash content 6.37%, yield 33.14%, iodine adsorption 1233 mg/g, methylene blue adsorption number 242 mg/g, Langmuir surface area 1497.52 m2/g and BET surface area 1076.15 m2/g. Both of four and five years of wood had the same carbonization and activation optimum-condition. The characteristics of resulting activated carbon closed to the commercial activated carbon. It is concluded that Eucalyptus camaldulensis Dehnh. wood could a suitable precursor for activated carbon production by using this research as a guideline